Political theologies and development in Asia : Transcendence, sacrifice, and aspiration - Feener, R. Michael; Fountain, Philip; Bolotta, Giuseppe (Book collections on Project MUSE., 2020)
A timely reassessment of the critical potential for political theology, this volume expands beyond the tendency to focus on the (post-)Christian West to open new lines of investigation. Through detailed empirical studies of development in Asia the chapters cast new light on the entanglements between religion and politics in this diverse region.